Optimasi Keputusan Metode Persalinan dengan Algoritma C4.5 - Alfianah, Adinda Bunga; Pratama, Mudafiq Riyan; Yunus, Muhammad; Vestine, Veronika (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
In 2018, the Indonesian Ministry of Health conducted a survey revealing that the rate of deliveries via Caesarean Section (C-Section) had exceeded the WHO's maximum standard of 17.6%. At Aulia Hospital in Pekanbaru, the prevalence of C-Sections reached 76% per 1000 births, significantly higher than the international benchmark. This study aims to analyze the factors influencing delivery methods using the C4.5 algorithm. The research employs a quantitative analytic approach with Secondary Data Analysis (SDA). A dataset of 500 records with 11 variables was utilized, including maternal age, gestational age, hypertension, hemoglobin, glucose levels, delivery history, fetal position, Cephalopelvic Disproportion (CPD), premature rupture of membranes (PROM), oligohydramnios, and estimated fetal weight (EFW). The C4.5 algorithm demonstrated 92% accuracy in predicting delivery methods, with a precision of 75%, indicating its ability to correctly identify necessary C-Sections. Furthermore, it achieved a recall of 100%, reflecting its effectiveness in identifying all actual C-Section cases. The rule tree analysis highlighted delivery history as the primary determinant in selecting the delivery method. These findings are expected to support medical decision-making processes regarding delivery methods and improve the management of high C-Section rates.